Gradient Studies Reveal the True Drivers of Extreme Life in the Atacama Desert. Issue 3 (4th March 2022) - Boy, D.; Moeller, R.; Sauheitl, L.; Schaarschmidt, F.; Rapp, S.; van den Brink, L.; Gschwendtner, S.; Borquez, R. Godoy; Matus, Francisco J.; Horn, M. A.; Guggenberger, G.; Boy, J.
Abstract: Studies of hyper‐arid sites contribute to our understanding on how life adapted to extreme conditions. They are often used to further deduce implications for extraterrestrial biology by the so‐called analogue site‐approach. The Atacama Desert, Chile, is one of the most prominent analogue sites despite its neighboring productive ecosystems due to its hyper‐aridity and geochemical features resembling Martian environments. We hypothesize that many drivers of extremophile life in analogue sites are only mistakenly attributed to aridity alone, thus obscuring a clear view of the far more complex process interactions originating in nearby earthly ecosystems. To test this, we investigated 54 soil profiles up to 60 cm of soil depth along of four transects in the Atacama Desert, either running parallel (S‐N) or perpendicular (W‐E) to the Andes. Our objective was to reveal the processes controlling the formation of soil organic carbon (SOC) as the most reliable proxy for microbial life in order to understand the boundary conditions of life in extreme habitats. Further, we aimed at identifying analogue sites as uncompromised as possible by external influences of for example, vegetated or marine ecosystems. We found a mixture of influences driving habitable conditions on gradients perpendicular to the Andes, for example, fog and precipitation scavenging caused by altitudinal variations and differing proximity to the Pacific Ocean, while transects parallel to the Andes were much less biased by external factors. Our results show that studies on life under extreme conditions should clarify the explanatory strength of the investigated factors by a gradient study approach. Plain Language Summary: Being the driest desert on Earth, the Atacama Desert is often regarded as resembling the living conditions on Mars making it a so‐called analogue site. Analogue sites are used to learn about the boundary conditions of microbial life and also help at understanding the evolution of life. The Atacama Desert is a hyperarid place alike Martian environments, but is influenced by factors clearly not occurring on Mars, for example, a highly productive Ocean nearby. Thus, if one wants to learn about the effects of aridity on the microbial life alone, an exclusion of other gradual influences is necessary. We aimed at identifying genuine aridity gradients and distinguishing them from gradients influenced by multiple drivers. We found that parallel to the Andes, a true climatic gradient with precipitation being the only changing parameter exists, while perpendicularly directed gradients displayed a mixture of influences. Future research on life along aridity gradients in the Atacama are most promising in the Longitudinal Valley to ensure a genuine climatic gradient. With this study, we hope to disentangle the multiple drivers which could be misleadingly interpreted as aridity features and highlight the chances of gradient approaches to ensure fair conclusions about driving factors in extreme environments. Key Points: Gradient studies are more suitable to elucidate the boundaries of habitability of extreme habitats as compared to non‐gradual studies At the Atacama, transects perpendicular to the Andes displayed multiple drivers of aridity while gradients parallel were much less biased Honest analogue research has to clearly allot the contribution of external sources, which otherwise results in questionable conclusions